Anti-candidal activity of crude extracts and compounds from Dipterocarpus verrucosus Foxw. Ex Sloot, Dipterocarpus cornutus Dyer and Dipterocarpus crinitus Dyer - Mohd Zain, Wan Zuraida Wan; Yusoff, Nor Asma Husna; Rukayadi, Yaya; Aziman, Nurain; Windayani, Neneng (Malaysian Institute of Chemistry, 2024)
Dipterocarpus, commonly known as 'keruing,' is an important source of dammarane and contributes to a highly valuable economic plant in Southeast Asia. A preliminary study revealed that this plant is rich in phenolic compounds and potential antimicrobial properties. Thus, the stem bark of three Dipterocarpus species (Dipterocarpus verrucosus, Dipterocarpus cornutus, and Dipterocarpus crinitus) has been extensively studied chemically and biologically. The methanol extract was isolated using multiple chromatography techniques, and the structural elucidation of the compounds was characterized using UV, IR, NMR (1d &2D), HRESI-MS, and comparison with literature. The anticandidal activity of the methanolic crude extracts and compounds was determined using the disc diffusion method, Minimum Inhibitory Concentration (MIC), Minimum Fungicidal Concentration (MFC), and time-kill assay against pathogenic strains, namely Candida glabrata. In this study, three crude extracts and 12 phytochemicals of consisting of nine stilbenoids (viniferin, ampelopsin A, α-viniferin, davidiol A, stenophyllol B, ampelopsin E, vaticanol B, diptoindonesin E, Hemsleyanol D, two phenolic compounds (bergenin, scopoletin) and one compound from terpene (β-sitosterol glucoside) were tested for their anticandidal activity. The disc diffusion method result showed that ε-viniferin was more susceptible to C. glabrata than other compounds; thus, this compound was selected for time-kill assay. The MIC and MFC ranged from 62.5 to 500 ppm. Time-kill curves demonstrated that ε-viniferin could inhibit C. glabrata strains at 500 ppm, after 120 min of treatment with a significant reduction of more than 3 log10 reduction. Results revealed the potential of viniferin isolated from Dipterocarpus to be developed as an anticandidal agent against C. glabrata.